DAYA SAING BAHASA INDONESIA DI ERA INDUSTRI KREATIF (STUDI PERBANDINGAN TERHADAP PELABELAN PRODUK PADA UMKM MAHASISWA UNIVERSITAS BANGKA BELITUNG) - Hartati, Lasmi; Rozi, Rozi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2022)
Indonesian is the national language for Indonesia. The use of Indonesian is important in various situations and conditions. Various kinds of tribes and cultures, Indonesian as an intermediary to become a single unit. One of the minimal applications of Indonesian is in product labeling. Therefore, this study aims to compare the competitiveness of the Indonesian language in the era of the creative industry with the main focus of this research comparing the competitiveness of using foreign languages with Indonesian in product labeling in Pangkalpinang, especially in UMKM students of the Faculty of Economics, Bangka Belitung University. This study focuses on the context of the competitiveness of the Indonesian language on MSME product labels. This study uses a qualitative-comparative design with observation and interview methods. This study describes a comparison of products that use foreign labeling. The findings show that products with foreign language labels are higher than Indonesian. The use of foreign languages for product labeling can result in a decrease in the value and competitiveness of the Indonesian language, especially in Pangkalpinang.Keywords: competitiveness, Indonesian language, creative industry